Effect of fluid shear stress on the internalization of kidney-targeted delivery systems in renal tubular epithelial cells - Yingying Xu; Shuo Qin; Yining Niu; Tao Gong; Zhirong Zhang; Yao Fu (Elsevier, 2020)
Renal tubular epithelial cells (RTECs) are important target cells for the development of kidney-targeted drug delivery systems. Under physiological conditions, RTECs are under constant fluid shear stress (FSS) from original urine in the renal tubule and respond to changes of FSS by altering their morphology and receptor expression patterns, which may affect reabsorption and cellular uptake. Using a microfluidic system, controlled shear stress was applied to proximal tubule epithelial cell line HK-2. Next, 2-glucosamine, bovine serum albumin, and albumin nanoparticles were selected as representative carriers to perform cell uptake studies in HK-2 cells using the microfluidic platform system with controlled FSS. FSS is proven to impact the morphology of HK-2 cells and upregulate the levels of megalin and clathrin, which then led to enhanced cellular uptake efficiencies of energy-driven carrier systems such as macromolecular and albumin nanoparticles in HK-2 cells. To further investigate the effects of FSS on endocytic behavior mediated by related receptors, a mice model of acute kidney injury with reduced fluid shear stress was established. Consistent with in vitro findings, in vivo studies have also shown reduced fluid shear stress down-regulated the levels of megalin receptors, thereby reducing the renal distribution of albumin nanoparticles. Key words: Fluid shear stress, Kidney-targeted drug delivery, HK-2 cells, Acute kidney injury